Relationship between education and cognitive performance among healthy Malay adults (Hubungan antara pendidikan dan prestasi kognitif dalam kalangan dewasa melayu sihat) - Hamzah A.I.Z.A.; Bakar Z.H.A.; Sani N.F.A.; Tan J.-K.; Damanhuri M.H.A.; Rani M.D.M.; Noh N.A.; Razali R.; Mohamad M.; Makpol S.; Mazlan M.; Hamid H.A.; et al. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus